2021
DOI: 10.3390/ijms222413372
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of RGF/GLV/CLEL Peptide Hormones and Their Roles in Land Plant Growth and Regulation

Abstract: Rooting is a key innovation during plant terrestrialization. RGFs/GLVs/CLELs are a family of secreted peptides, playing key roles in root stem cell niche maintenance and pattern formation. The origin of this peptide family is not well characterized. RGFs and their receptor genes, RGIs, were investigated comprehensively using phylogenetic and genetic analyses. We identified 203 RGF genes from 24 plant species, representing a variety of land plant lineages. We found that the RGF genes originate from land plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…RGFs also play a critical role in the regulation of plant gravitropism [ 116 , 117 ], the formation of lateral roots and root hairs [ 118 , 119 , 120 ], and are sensitive to phosphate deprivation [ 82 ]. The results of a study using synthetic RGF peptides (DYAEPDTHPPESN, YSPAKRKPPIHN, DYKSPRHHPPRHN and, DYHSVHRHPPTHN) [ 121 ] showed that all synthetic peptides, both tyrosine sulfated and proline hydroxylated, can cause wild-type root sway in seedlings. Gravistimulation assays have shown that these peptides influence the gravitropic response of the root.…”
Section: Rgf Peptides Regulating the Root Developmentmentioning
confidence: 99%
“…RGFs also play a critical role in the regulation of plant gravitropism [ 116 , 117 ], the formation of lateral roots and root hairs [ 118 , 119 , 120 ], and are sensitive to phosphate deprivation [ 82 ]. The results of a study using synthetic RGF peptides (DYAEPDTHPPESN, YSPAKRKPPIHN, DYKSPRHHPPRHN and, DYHSVHRHPPTHN) [ 121 ] showed that all synthetic peptides, both tyrosine sulfated and proline hydroxylated, can cause wild-type root sway in seedlings. Gravistimulation assays have shown that these peptides influence the gravitropic response of the root.…”
Section: Rgf Peptides Regulating the Root Developmentmentioning
confidence: 99%